(untitled) (The Review of Diabetic Studies, 2025)
Background: Type 1 diabetes mellitus (T1D) is a chronic autoimmune condition requiring lifelong insulin therapy. Despite advances in insulin delivery, achieving near-physiological glucose control remains challenging due to glycemic variability and hypoglycemia risk. Closed-loop artificial pancreas (AP) systems integrate continuous glucose monitoring, insulin pumps, and automated algorithms to maintain glucose within target ranges. Objective: To systematically evaluate the efficacy and safety of closed-loop insulin delivery systems in individuals with T1D, focusing on glycemic outcomes, time-in-range (TIR), HbA1c reduction, and adverse events. Methods: A systematic search was conducted in PubMed, Scopus, Web of Science, Embase, and Google Scholar for studies published between 2010 and 2025. Randomized controlled trials, crossover trials, and single-arm intervention studies assessing closed-loop or hybrid AP systems in T1D populations were included. Data extraction focused on study design, participant characteristics, algorithm type, glycemic outcomes, and safety. Results: Ten studies encompassing 14–124 participants aged 6–75 years met inclusion criteria. Closed-loop systems consistently improved TIR by 6–15 percentage points, reduced HbA1c by 0.3–0.6%, and decreased hypoglycemia by 30–60%. Hybrid and model predictive control algorithms demonstrated comparable efficacy, while adaptive systems allowed personalized basal insulin adjustment. Adverse events were minor and infrequent; no serious hypoglycemia or diabetic ketoacidosis was reported. Improvements were observed across pediatric, adolescent, and adult populations under both supervised and home conditions. Conclusion: Closed-loop artificial pancreas systems significantly improve glycemic control and reduce hypoglycemia risk in T1D. Their safety, usability, and positive impact on quality of life highlight their potential as a standard component of modern diabetes management.